2023
DOI: 10.3389/fgwh.2023.1027409
|View full text |Cite
|
Sign up to set email alerts
|

Examining the gaps in perinatal mental health care: A qualitative study of the perceptions of perinatal service providers in Canada

Abstract: In Canada, access to perinatal mental health services is disparate across districts, regions, provinces, and territories. Questions remain as to how gaps in service are being experienced by Canadian service providers and clinicians. This paper examines three key questions: 1) What are the experiences of care providers with respect to the screening, identifying, and managing perinatal mental health disorders? 2) What gaps in perinatal mental health care have been identified? and 3) What approaches have been tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Qualitative findings from our study extend these findings and indicate the need for centralized processes to support care coordination, referrals, and education. Indeed, adopting a national strategy to provide a coordinated approach to PMH care holds the potential to harmonize screening practices and care standards across provinces and territories, while also enhancing integration and access to care through centralized funding and resource allocation [ 20 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Qualitative findings from our study extend these findings and indicate the need for centralized processes to support care coordination, referrals, and education. Indeed, adopting a national strategy to provide a coordinated approach to PMH care holds the potential to harmonize screening practices and care standards across provinces and territories, while also enhancing integration and access to care through centralized funding and resource allocation [ 20 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the majority of care providers (87%) reported that many parents encounter significant barriers to accessing perinatal services, including limited availability, out-of-pocket costs, and a failure to address cultural safety [ 20 ]. As such, PMH services remain uncoordinated, with access often determined by ‘postal code lottery’, with those from urban, affluent, and well-resourced communities faring better than those from historically marginalized communities [ 20 , 22 ]. Because available services are often narrow in focus and ignore the broader social determinants of health—such as income and housing—pathways to screening, treatment, and follow-up tend to be unclear and difficult to navigate [ 20 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within science, integration from diverse disciplines and building transdisciplinary evidence is critical to address the challenge of promoting neurobehavioral development globally. That researchers have an important responsibility in perinatal mental healthcare and in communicating results concerning perinatal environmental exposure, neurodevelopment, and interventions is emphasized in several fields [15 ▪ ,118,154,193,205,208,230,240–251,257 ▪ ]. Community-oriented participatory research with key stakeholders [252], and community engagement [238] to gather ‘bottom-up’ concerns from parents and practitioners [253] is needed, and may contribute to advocacy [239,253].…”
Section: Global Mental Health and The Promotion Of Neurobehavioral De...mentioning
confidence: 99%
“…Further, screening provides signi cant cost savings [4][5][6][7][8] by ensuring that only those who require more time and labour-intensive diagnostic assessments are offered them [4,[8][9][10]. Although screening for mental health conditions has been shown to lead to improved mental health even in the absence of a clear pathway to treatment [11,12], there are still several gaps in screening for mental health conditions in Canada, particularly in the perinatal period [13].…”
Section: Introductionmentioning
confidence: 99%